Supporting High-Risk Percutaneous Coronary Interventions With Mechanical Devices - Wilkinson, Stephen E. (JACC Case Rep, 2020)
The use of mechanical circulatory support to maintain appropriate hemodynamics in high risk percutaneous coronary intervention cases is a new frontier. Treatment of cases that were once considered prohibitive may now be possible. Due to a paucity of data, guidelines offer no guidance about the use of mechanical circulatory support in such cases. This case, the first documented case of extracorporeal membrane oxygenation support for percutaneous coronary intervention (PCI) of a vein graft supplying the entire coronary circulation, adds to the medical literature demonstrating a likely benefit in the use of mechanical support during high risk PCI in patients without shock. (Level of Difficulty: Intermediate.)